Analisis Hubungan Frekuensi-Magnitudo Gempa Bumi di Bali dan Sekitarnya - Wandono Wandono; Sri Widiyantoro; Gunawan Ibrahim; Edy Soewono (Institut Teknologi Bandung, 2004)
We mapped the 3-D b-value variation in Bali and its vicinity through analyzing the frequency-magnitude relation. A high b-value anomaly is observed beneath the Lombok volcanic arc at 90-180 km depth interval. It is related to the zone of partial melting of basaltic magma on the subducted slab of Indian oceanic plate beneath the Eurasian plate in Nusa Tenggara Barat. This analysis supports the hypothesis about the existence of melting point on the slab.